036. Sclerotic Therapy as The Management Of Arteriovenous Malformation on Hand: A Case Report - Arnaya, Agung Aditya; Wibawa, IGAB Krisna (JBN (Jurnal Bedah Nasional); Vol 8 No 2 (2024): Proceeding The 2nd National Conference of Indonesia Surgical Education, 2024)
Background : An arteriovenous malformation (AVM) is an abnormal connection between arteries and veins, bypassing the capillary system. There are a number of consequences associated with this illness, such as bleeding and neurological impairments. The situation is complex, which emphasizes the necessity for individualized treatment plans. This case report a 18 years old female with AVM condition. Case: A 18 years old female was admitted to to Prof. IGNG Ngoerah General Hospital with a chief complaint of lump on the left finger. The lump on the left finger has been felt since >10 years ago. The lump appeared suddenly and went bigger each day. Complaints worsened until the patient felt pain in the left finger. On examination of the local status, multiple masses were found on third and fourth digits of the left hand, with unclear border and vein ectasis. MSCT Angiography of the left superior extremity found a soft tissue image of hemangioma on the palmar aspect and interdigiti III-IV to the palmar-dorsal aspect of digit III and the palmar aspect of digiti IV of the left hand and multiple non-suspicious lymphadenopathy in the left axilla region. The scleroterapy treatment was performed and 3 months results shown decreased size of the masses without any complication. Conclusion: An arteriovenous malformation (AVM) of the left hand fingers is a rare case found in Prof Ngoerah Hospital. The sclerotic therapy found to be an effective management for this case.